Effect of Tillage, Residue and Nitrogen Management on Soil Water Dynamics and Water Productivity of Wheat in an Inceptisol - P. Krishnan, A. Sarangi and S.P. Datta, Alka Rani, K.K. Bandyopadhyay (Journal of the Indian Society of Soil Science, 2019)
A field experiment was conducted during rabi season for two consecutive years (2014-15 and 2015-16) on wheat crop in a sandy loam soil (Typic Haplustept) at the research farm of Indian Agricultural Research Institute (IARI), New Delhi with the objective of studying soil water dynamics and water productivity of wheat under different tillage, residue and nitrogen (N) management practices. The treatments comprising of two levels of tillage as main plot i.e. conventional tillage (CT) and no tillage (NT), two levels of residue as subplot i.e. maize residue @ 5 t ha-1 (R+) and without residue (R0)), and three levels of N as sub-sub plot i.e. 60, 120 and 180 kg N ha-1, representing 50% (N60), 100% (N120) and 150% (N180) of the recommended dose of N for wheat, respectively were evaluated in a split-split plot design with three replications. Results showed that there was increase in the profile moisture storage by 7.7 per cent under crop residue mulch. The evaporative flux was lower by 23.9 per cent but deep percolation flux was higher by 8.3 per cent under mulching than without mulch treatment. The water productivity of wheat was not influenced by tillage but increased significantly with the increase in N levels. During high rainfall year, the effect of crop residue mulch on water productivity was not significant but it increased significantly during low rainfall year.